RESEARCH OF THE KINETICS OF GLOWING OF LED LIGHT SOURCES - ANDRIICHUK, VOLODIMIR; NAKONECHYI, MYROSLAV; FILIUK, YAROSLAV; KOSTYK, LIUBOV; OSADTSA, YAROSLAV (Herald of Khmelnytskyi National University. Technical sciences, 2023)
Among the artificial light sources, LED sources (LED) are becoming the most common. For their power supply in lighting systems, pulsed power supply with pulse width modulation is used. To ensure high energy efficiency and reliability of LED lighting devices, it is necessary to have information about the kinetics of both electrical and light pulses. Currently, this problem is not sufficiently covered in the literature. The paper presents the results of the study of the energy and dynamic characteristics of FYL-3014 and ARPL-1W white light LEDs with a color temperature of 3000 K and 6000 K when they are powered by P-shaped pulses with a frequency from 1 to 400 kHz. Based on spectral and dynamic studies of the light flow, it is shown , that their white glow is obtained due to the superimposition of the radiation of the InGaN-AlGaN heterostructure in the blue spectral region with a maximum of 450 nm and the YAG:Ce photoluminophore with high quantum efficiency and a wide band in the yellow-orange spectral region (500-710 nm). Based on the obtained oscillograms, it was established that the rise and fall of the light flux in both bands is described by an exponential dependence. The time constants for the rise and fall of the light flux in the yellow-orange band of photoluminescence of a warm-white LED exceed twice the time constants for cold-white (1050 ns). With an increase in the frequency of pulsed power supply, the rise and fall time constants of the light flux in this band for both types of LEDs decrease to 350-400 ns at 400 kHz. When the amplitude of the voltage and current pulses changes, the rise and fall time constants of the light flux do not change. The most energetically favorable frequency range of pulsed power supply of lighting installations with FYL-3014 and ARPL-1W LEDs of white light is from 10 to 100 kHz and filling from 0.3 to 0.95.
Keywords: LED; pulse width modulation; energy efficiency; attenuation coefficient